Research of crises of professional formation from the position of subject-active approach - Miliutina, Kateryna; Rubel, Nataliia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
In the article are represented results of empirical research of anxiety features and life goals of personality in professional development crisis. Our sample included 80 persons in the age 17-35 years. It was divided on two groups: first group consisted of 34 people, students of 1-3 courses, the second group consisted of 46 people that were changing their profession and are actually practicing new trade. We used anxiety test of Spilberger-Hanin to explore level of individual and situational anxiety. In addition, we used “Life goals of personality” method that was developed by laboratory of social psychology ISPP NASU led by T. M. Tytarenko. With the help of this method, we explored characteristics of life goals of our sample. It was found that there is a significant difference by Rs criterion on the level p ≤ 0,05 between two groups on a scale “Operational characteristics of life goals”. Among working people prevail doubts that they can cope with difficulties, thoughts that success is just an accident, orientation on “need”, but not “want”. In students group we can see lack of stability and flexibility in solving life tasks. There is straight correlation between motivational directions level and individual anxiety level on the group of working people (p < 0,01). It means growing of inside tension in the presence of motivational directions number increasing. We can assume that motivational direction is some sort of coping-strategy that is using by anxious individuals to put their lives in order. In that way they try to create “image of desired life”, that combines expectations, demands and intentions, determining choice of life-realization strategy. In both groups was identified inverse correlation between attitude to the future and individual anxiety (P < 0,01). Operational characteristics of life goals inversely proportional to anxiety level in both groups. That means, that recognition of self-meaning in life-realization, orientation on own plans and needs and ability to take responsibility are low anxiety level related factors. This results gives us an opportunity to say that higher identity, own life goals realization, sense of resilience, life integrity, using of flexibility and activity strategies helps to cope with anxiety during professional crisis.
Keywords: act; crises; professionalization; socialization; anxiety; students